Temporary captive population and rapid population recovery of an endemic flightless rail after a rodent eradication operation using aerially distributed poison bait. (December 2016) - Oppel, Steffen; Bond, Alexander L.; Brooke, Michael de L.; Harrison, Gavin; Vickery, Juliet A.; Cuthbert, Richard J.
Abstract: Operations to eradicate non-native invasive predators from islands generally have large conservation benefits, but may put native species at risk where poison bait is used for eradication. Whether the risk of unintentionally poisoning native species can be effectively reduced or mitigated is a critical determinant in deciding the potential utility of an eradication operation. Here, we describe the mitigation measures adopted for an endemic flightless rail species, the Henderson Crake ( Zapornia atra ), during a rodent eradication operation on Henderson Island, South Pacific, where aerially applied brodifacoum bait was used in 2011. We established a secure temporary in situ captive population of 108 birds, of which 22 individuals died due to initial complications in accepting artificial food. We used point counts and radio-tracking to estimate the effects of the eradication operation on the wild population of Henderson Crakes, and found the expected high mortality (83–97%) due to primary poisoning. Despite this mortality, the Henderson Crake population recovered from very low levels in 2011 (9 birds at 25 point count locations) to 2015 numbers similar to those in the 1980s and 1990s (228 birds at 25 point count locations), despite the eradication operation failing to remove all rats from Henderson Island. The recovery of the natural population was supplemented by 89 individuals released from temporary captivity 2–3 months after the eradication attempt. We conclude that, despite the high mortality of Henderson Crakes during the eradication attempt, the mitigation measures taken to safeguard this endemic species were effective and contributed to the rapid recovery of the species following the eradication operation.